Efficient D2D Discovery Scheme for Channel Measurement of Interference Alignment - Zhanjun Liu; Yunpeng Li; Zhonghua Yu; Yue Shen (Universitas Ahmad Dahlan, 2016)
Device-to-device (D2D) communications have the potential to improve spectrum efficiency and link capacity by allowing nearby devices to communicate directly with each other on the licensed frequency bands. Hence, co-channel interference (CCI) among D2D users are major issues to be solved when they are utilizing the same frequency bands. Consequently, interference alignment (IA) as an effective interference management approach has been implemented to the D2D communications for the frequency sharing. However, the measurement of channel state information (CSI) between transmitter and receiver of a D2D pair and cross-channel state information (C-CSI) among D2D pairs are the major issues that need to be resolved for the implementation of IA from theory to practical. Therefore, in this paper, we propose an effective D2D discovery scheme to overcome this problem, which can measure the CSI and C-CSI based on the transmission of discovery messages. Simulation results show that, under perfect conditions, even though the proposed D2D discovery scheme increases the needed time slots to establish D2D communications compared with the conventional D2D discovery without considering IA by 6.2%, it increases the throughput up to 50% than the conventional D2D communications without considering IA, i.e., it improves the spectrum efficiency.